Experimental and Numerical Simulations at Sonic and Supersonic Mach Numbers for Area Ratio 7.84 - Khan, Ambareen; Mazlan, Nurul Musfirah; Ismail, Mohd Azmi; Akhtar, Mohammad Nishat (CFD Letters, 2021)
Sudden expansion is a common phenomenon found in automobiles, aerospace vehicles and in combustion chambers. Flow separation occurred in the sudden expansion area will influence base pressure either the flow is sonic or supersonic. Therefore, an experimental and numerical works were carried out to evaluate the base pressure variation with nozzle pressure ratio (NPR) in the range from 2 to 8 for a fixed L/D ratio. The experimental investigation and simulations were performed at Mach numbers ranging from 1 to 2.5 for suddenly expanded square duct of 28 mm side. The results indicate that there is marginal discrepancy in the simulation and experimental results. It is found that the base pressure continues to decrease with the increase in NPR, and this trend continues even when the jets are under-expanded due to the vast area ratio of the enlarged duct. The base pressure values obtained from numerical simulations are marginally higher than the experimental values even though all the other parameters are the same, as the values of the simulation were taken for the entire region of the base whereas, the experiments were conducted at selected points in the base area. Another reason for the discrepancy is the error in the measurements as well as the losses occurring during the flow through the taps.